Does Hindfoot Valgus Deformity Affect the Distal Tibiofibular Syndesmotic Space?. Issue 4 (22nd October 2020) - Li, Shuyuan; Silva, Thiago A.; Baumfeld, Daniel; Mansur, Nacime S.; Baumfeld, Tiago S.; Dibbern, Kevin N.; Lintz, Francois; Duchman, Kyle R.; Femino, John E.; Netto, Cesar de Cesar
Category: Hindfoot; Ankle; Ankle Arthritis; Sports Introduction/Purpose: Severe hindfoot valgus deformity has been reported as one of the main causes of sinus tarsi and subfibular impingement in patients with adult acquired foot deformity (AAFD). Chronic Impingement and overload of the talus and/or calcaneus on the articular surface of the distal fibula can potentially lead to distraction stresses on the distal tibiofibular syndesmosis (DTFS). However, to the authors knowledge, no direct assessment of DTFS widening in patients with AAFD has been reported in the literature. The purpose of this study was to evaluate the correlation between hindfoot alignment and DTFS widening using weightbearing computed tomography (WBCT) images, and to compare the results between AAFD patients and controls. Methods: In this case-control study, we included 97 patients who underwent WBCT examination, 63 AAFD patients and 34 controls, with no history of major ankle trauma or surgeries of the foot and ankle. Hindfoot alignment was assessed using Foot and Ankle Offset (FAO) and the widening of the DTFS was evaluated by measuring the syndesmotic area (mm2) on axial plane WBCT images, at a level 1cm proximal to the apex of the tibial plafond. Controls were defined as patients with no clinical AAFD and normal FAO values (from -0.6 to 5.2). FAO and DTFS area measurements were compared by paired T-tests and ANOVA. Correlation between variables was assessed by bivariate linear regression. A partition predictive model was used to define threshold values of FAO that would influence DTFS area measurements. P-values of less than 0.05 were considered significant. Results: AAFD patients demonstrated significantly increased mean values for DTFS area (90.0mm2; 95%CI, 84.3 to 95.7) when compared to controls (79.9 mm2; 95%CI 73.8 to 85.9), p=0.03. However, no significant direct linear correlation was found between FAO and DTFS area measurements (p=0.07) in the bivariate analysis. The partition predictive model demonstrated that two threshold values of FAO would significantly influence DTFS area (R2=0.14): when FAO was <7 the average DTFS area was 80.8mm2 (SD 17.8), when FAO was >7, the mean DTFS area was 92.7mm2 (SD 22.4). Interestingly, when assessing patients with more severe valgus (FAO>7), the DTFS area measurements were even higher when FAO values were in between 7 and 9.3 (average, 104.6mm2, SD 22.5), but decreased when FAO>9.3 (average, 88 mm2; SD 22.3). Conclusion: This is the first study to compare distal tibiofibular syndesmotic widening in patients with AAFD and controls. We found that AAFD patients had significant syndesmotic widening when compared to controls, with a difference of about 10 mm2 in the measured area. More than that, we found that AAFD patients with FAO in between 7 and 9.3 would demonstrate the largest amount of syndesmotic widening. However, no direct linear correlation was found between FAO and syndesmotic area measurements. Our findings suggest that increased hindfoot valgus deformity may have negative biomechanical impact on syndesmotic alignment, with increased stresses and resultant widening.